Effects of Continuing Oral Risperidone vs. Switching from Risperidone to Risperidone Long-Acting Injection on Cognitive Function in Stable Schizophrenia Patients: A Pilot Study - Hori, Hikaru; Katsuki, Asuka; Atake, Kiyokazu; Yoshimura, Reiji (Frontiers in Psychiatry, 2018)
Objectives: Risperidone is the first new generation antipsychotic drug to become available as a long-acting injection (LAI). The purpose of this study was to evaluate the effects of switching from oral risperidone to risperidone LAI (RLAI) on cognitive function in stable schizophrenia patients compared with the effects of continuing oral risperidone. Methods: Sixteen stable patients who had received risperidone monotherapy for at least 3 months were enrolled (the RLAI group). Before and 24 weeks after switching to RLAI, the Japanese-language version of the Brief Assessment of Cognition in Schizophrenia (BACS-J) and the Positive and Negative Syndrome Scale (PANSS) were administered. To exclude the possibility of learning effects on the BACS-J results, 14 age- and sex-matched patients with stable schizophrenia who continued oral risperidone treatment were also assessed (the RIS group). Results: The two groups did not differ with respect to changes in the PANSS score, and no emergent side effects, including extrapyramidal symptoms, were observed. The BACS-J score for verbal memory exhibited greater improvement in the RLAI group than in the RIS group (p=0.047). Conclusions: The results of this preliminary study suggest that switching from oral risperidone to RLAI may improve verbal capability more than continuing with oral risperidone. However, these findings must be replicated in a larger, double-blind study.